Cyclic stretch of either PNS or CNS located nerves can stimulate neurite outgrowth - Kampanis, Vasileios; Tolou Dabbaghian, Bahardokht; Zhou, Luming; Roth, Wolfgang; Puttagunta, Radhika (Cells, 2021)
The central nervous system (CNS) does not recover from traumatic axonal injury, but the peripheral nervous system (PNS) does. We hypothesize that this fundamental difference in regenerative capacity may be based upon the absence of stimulatory mechanical forces in the CNS due to the protective rigidity of the vertebral column and skull. We developed a bioreactor to apply low-strain cyclic axonal stretch to adult rat dorsal root ganglia (DRG) connected to either the peripheral or central nerves in an explant model for inducing axonal growth. In response, larger diameter DRG neurons, mechanoreceptors and proprioceptors showed enhanced neurite outgrowth as well as increased Activating Transcription Factor 3 (ATF3).